Legal Responsibility of Sub-District Social Welfare Workers in The Social Protection of Vulnerable Communities in Lubuklinggau City - Dedi Afriyansyah (CV. Pustaka Parawali, 2025)
This research aims to analyse the legal responsibilities of Sub-district Social Welfare Workers (TKSK) in the social protection of vulnerable communities in Lubuklinggau City. Vulnerable communities, including the elderly, people with disabilities, and other marginalised groups, often experience various challenges and obstacles in accessing social services. TKSK plays an important role in implementing social protection programmes aimed at improving community welfare. The contribution of this research is to provide in-depth insight into the role and challenges of TKSK in the context of social protection and offer policy recommendations that can strengthen the implementation of social protection programmes, especially for vulnerable communities in Lubuklinggau City. The results of this research are expected to be an important reference for policy makers in designing a more inclusive and effective social protection strategy. Methods This research uses a normative juridical approach by examining the laws and regulations governing the responsibilities of TKSK as well as practices in the field. The results show that although TKSK has a strong legal basis, there are various obstacles in the implementation of its responsibilities, such as lack of resources, suboptimal coordination with other agencies, and challenges in programme socialisation. Therefore, strategic steps are needed to strengthen the role of TKSK in providing effective social protection for vulnerable communities, including capacity building and understanding of community social rights. This research is expected to contribute to the development of social protection policies in Lubuklinggau city.